The orchids, a sustainable alternative for the development of ecotourism. Case study, Carchi province, Ecuador - Guevara Rosero, Jairo Mauricio; Leyva Vásquez, Noryuan Carlos; Caicedo Rosero, Diego Marcelo (SATHIRI, 2019)
The research completed proposes a development of thematic tourist route, taking advantage of the emblematic natural resource "the orchids" to develop the tourist activity in Carchi province, Ecuador. The design process is described through methodologies established by the Tourism Ministry to determine tourist attractions and their hierarchies. With the geographical representation systems, the route is determined and each point of tourist interest are represented. Marketing strategies are established to promote the route, as alternative for the economic development through sustainable ecotourism. Finally, a tourist rout is based with the highlights natural"™s values of the region, diversifying the tourist offers in the province, to become an important element for the development of the communities, with the linkage of its inhabitants and the use of existing natural resources and improve living conditions and encourage new ventures, as well as, the conservation of the environment.